A Comparative Palynofacies Study of Two Methods Used for Source Rock Validation. A Case Study From a Mississippian Succession on Spitsbergen - Hansen, Tone Hetland (The University of Bergen, 2017)
This study is conducted on the analysis of twenty-nine kerogen slides of Tournasian and Visean age. The outcrop samples were collected from the Hoelbreen and Birger Johnsonfjellet Members in the Birger Johnsonfjellet section on Spitsbergen, Svalbard. The main aim of this study was to test two different methods for palynofacies analysis using the scheme after Bujak et al. (1977): point counting and a relative area measurement method using the free image analysis software ImageJ. A secondary minor aim was to evaluate the hydrocarbon source rock potential of the organic matter from the studied samples. All five kerogen types defined for this study (hylogen, melanogen, phyrogen, AOM and pseudoAOM) were present in the twenty-nine samples, and most of the material was dark brown in colour. A pre-study to assess the validity of visual estimation of relative areas was first conducted. The number of fields of view that should be analysed to get a reliable result was estimated and concluded leading to that 60 frames were analysed per sample. Images captured with a camera connected to a transmitted light microscope were analysed using both methods, and a total of 1789 frames and 16 266 particles were counted, and their area measured. Fluorescence analysis was also conducted in order to clarify the presence of Botryococcus. The kerogen groups hylogen and pseudoAOM dominates the samples, with an increased amount of phyrogen recorded towards the top of the studied succession. The kerogen groups melanogen and Amorphous Organic Matter (AOM) were both poorly represented in these samples which all were terrestrially derived. An increasing amount of Botryococcus was observed in the upper part of the succession in the Birger Johnsonfjellet Member. This is also observed in previous studies of this formation.The average result based on the 29 slides studied herein did not reveal any significant difference between the two tested methods, however, analysis of each individual kerogen group revealed important differences: this included ...